Persepsi Milenial Terhadap Koperasi - Ardina, Sherrin Nur; Yanuar, Rahmat (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Cooperatives are business entities that are expected to be able to become the pillars of the national economy, but in fact cooperatives in Indonesia are not well developed. The purpose of this research is to identify millennial knowledge, attitudes and intentions towards cooperatives and to analyze the influence between knowledge and attitudes of the millennial generation on millennial intentions to encourage cooperative movements. This study used data from 158 economics and management students through an online survey using google form. The framework used in this study uses the TPB model from Ajzen but there are modifications to the knowledge variable. The analytical method used is descriptive analysis, different test (independent sample t test) and partial least square (PLS). The results showed that subjective knowledge and millennial attitudes towards cooperatives were in the sufficient category, while objective knowledge and millennial intentions towards cooperatives were in the good category, objective knowledge had a significant effect on subjective norms and behavior control, subjective knowledge had a significant effect on attitudes, subjective norms, and behavior control, while attitude has a significant effect on intention.